2011
DOI: 10.1016/j.gca.2010.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Growth rate of the preserved continental crust: II. Constraints from Hf and O isotopes in detrital zircons from Greater Russian Rivers

Abstract: Detrital zircons from the Ob, Yenisey, Lena, Amur, Volga, Dnieper, Don and Pechora rivers have been analyzed for U-Th-Pb, O and Lu-Hf isotopes to constrain the growth rate of the preserved continental crust in Greater Russia. Four major periods of zircon crystallization, 0.1-0.55, 0.95-1.3, 1.45-2.0 and 2.5-2.9 Ga, were resolved from a compilation of 1366 zircon U/Pb ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 76 publications
2
45
0
Order By: Relevance
“…Present day sands from the large rivers draining the East European Platform, contain dominant populations of Archean and Paleoproterozoic zircons (Safonova et al, 2010;Wang et al, 2011). The absence of Archean-Paleoproterozoic rocks in the Pontides and their presence north of the Black Sea coupled with the southeasterly paleocurrents measured in the eastern and central parts of the Çağlayan Basin indicate that these parts of the basin were sourced from north of the Black Sea.…”
Section: Archean and Paleoproterozoic Zirconsmentioning
confidence: 99%
“…Present day sands from the large rivers draining the East European Platform, contain dominant populations of Archean and Paleoproterozoic zircons (Safonova et al, 2010;Wang et al, 2011). The absence of Archean-Paleoproterozoic rocks in the Pontides and their presence north of the Black Sea coupled with the southeasterly paleocurrents measured in the eastern and central parts of the Çağlayan Basin indicate that these parts of the basin were sourced from north of the Black Sea.…”
Section: Archean and Paleoproterozoic Zirconsmentioning
confidence: 99%
“…This oxygen-isotope based criterion has subsequently been used in many other studies (e.g. Wang et al 2009Wang et al , 2011Lancaster et al 2011), typically revealing that crustal growth in any one particular region occurs in discrete episodes. Along with Hf isotopes, oxygen isotopes in zircon provide equivocal information, and thus their use as a binary discriminator is less than ideal (i.e.…”
Section: Crustal Growth Ratementioning
confidence: 99%
“…These have been used as a broad representation of the continental crust for studying its age and composition, and from this, the patterns of continental growth and evolution (e.g. Wang et al 2009Wang et al , 2011Iizuka et al 2010Iizuka et al , 2013. In this paper, we review some of the major contributions that zircon studies have made to our understanding of the formation and evolution of continental crust.…”
mentioning
confidence: 99%
“…It is argued that zircons from large rivers that drain large areas of continental crust provide the best way to obtain an unbiased and representative sample of the continental crust therein (e.g. Iizuka, 2005;Campbell and Allen, 2008;Wang et al, 2009;Iizuka et al, 2010;Wang et al, 2011;Yin et al, 2012;Iizuka et al, 2013). However, Allegre and Rousseau (1984) and Dhuime et al (2011) have demonstrated that continental erosion results in a distinct bias toward younger lithotectonic domains.…”
Section: Introductionmentioning
confidence: 99%